AUDEx – Automotive development in 1:x : angewandte Lehre und Forschung mit skalierten Fahrzeugmodellen - Eric Franz and Dirk Engel (VDI-Berichte, 2022)
At University of applied sciences Hamburg (HAW), „AUDEx (AUtomotive DEvelopment in 1:x)“ has been established to further improve the education of students and to familiarise them with actual industrial development processes. The aim of this project is to apply the acquired knowledge to "real" vehicles. To simplify the implementation, there are scale models of RC vehicles which, as “experience models”, allow a quick and uncomplicated implementation of own-developed functions and/or systems. By using these scaled vehicles and the DiL simulator, theoretical developments can be put into practice and personally experienced. In addition, the AUDEx project also offers the opportunity to be active in the current research fields like e.g., energy efficient vehicle or highly automated and autonomous driving.